The Influence of Government Policy and Service Quality on the Competitive Advantage of MSMEs through Product Innovation - Sholihin, Ustadus; Arida, Ririn Wahyu; Haryanto, Ferdyan Fais (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2025)
This study aims to evaluate the influence of government policies and service quality on the competitive advantage of Micro, Small, and Medium Enterprises (MSMEs) through the mediation role of product innovation in Kediri City. The study used a quantitative approach, collecting data through questionnaires distributed to 85 MSME actors who are members of the Indonesian Conveyance Entrepreneurs Association (IPHI) DPC Kediri City. Data analysis was conducted using the Partial Least Squares (PLS) method to test the relationships among variables in the research model. The study's results indicate that product innovation plays an important role in building MSMEs' competitive advantage. Government policies and service quality affect product innovation, but neither shows a significant direct effect on competitive advantage. Product innovation has been shown to mediate the relationship between service quality and competitive advantage, whereas the mediation role in the relationship between government policies and competitive advantage remains limited. These findings indicate that product innovation is a strategic element that needs to be strengthened to enhance MSME competitiveness. Therefore, policy support and improving service quality need to be directed to encourage the creation of relevant and sustainable innovations in the MSME sector.